DIGITAL INDIA REACHING TO SMALL, MARGINAL & WOMEN FARMERS - Patel, Amrit (International Journal of Research -GRANTHAALAYAH, 2016)
India has relatively much higher global hunger index than that in China. In last 25 years India could improve it from 31.2 in 1990 to 17.8 in 2014 as against 13.6 to 5.4 in China. Now when in September 2015 India has committed to achieve the United Nations General Assembly’s mandated Sustainable Development Goal-2 targets to “end hunger, achieve food security and improved nutrition, and promote sustainable agriculture” by 2030, it is necessary to analyze the strength and weaknesses of India’s agriculture. Potential for developing agriculture in India has been significant. However, agriculture is predominantly dominated by a larger number of small, marginal & tenant farmers, oral lessees, share croppers, agricultural laborers and those residing in desert, drought-prone, hilly and tribal areas in particular. It is in this context, this article attempts to highlight the immediate need to strengthen the Information and Communication Technology [ICT] to enable small, marginal and women farmers in particular in the light of measures already initiated by the government, NABARD and the private sector in developing farmer-friendly portals as an integral part of digital India project to accelerate farm productivity, production and profitability.